Cortical and subcortical gray matter alterations in first-episode drug-naïve adolescents with major depressive disorder. Issue 17 (10th December 2019) - Kim, Ji Hyun; Suh, Sang-il; Lee, Ho-Jun; Lee, Jong-ha; Lee, Moon-Soo
Abstract : Major depressive disorder is a major mental disorder affecting adolescents. Cortical thickness provides a sensitive measure of age-associated changes. Previous studies using cortical thickness analysis reported inconsistent results on brain structural changes in adolescent major depressive disorder. The neuroanatomical substrates of major depressive disorder in adolescents are not fully understood. We aimed to compare the anatomical structures of the brain in first-onset drug-naïve adolescents with major depressive disorder to normal controls. Twenty-seven first-episode drug-naïve adolescents with major depressive disorder and an equal number of age-matched control subjects were scanned on a 3T MRI scanner. Comparisons between those two groups were performed using surface-based morphometry analysis for cortical thickness and volumetric analysis of subcortical gray matter. The correlations between morphometric indexes and clinical measures (Hamilton depression rating scale score or children's depression inventory score) were also calculated. We found that the cortical area is thinner in major depressive disorder patients than in controls, specifically in the left occipital area (precuneus and cuneus, cluster-level family-wise corrected P < 0.05). The hippocampus volume was also smaller in major depressive disorder patients than in the control group. No significant correlations were found between morphometric indexes (average cortical thickness extracted from the left precuneus cluster and hippocampal volume) and clinical measures. The left occipital cortical regions may have a role in the pathophysiology of adolescent major depressive disorder, and the involvement of the hippocampus is important for pathogenic changes even in the early stages of major depressive disorder.